ANALYSIS OF SOLUTION OF THE MATHEMATICAL MODELS IN DYNAMICS - LABAŠOVÁ, Eva; TRUBENOVÁ, Jaroslava (Trends in education, 2009)
In many technical branches, computer mathematical models describing and examining real object behaviour are used during problem solving. Mathematical model analysis represents a solution of the given system of equations. This contribution suggests an application of mathematical knowledge for students of technical universities. In particular, it points at utilisation of knowledge obtained in the area of differential equations, in solution of the solid body oscillation movement.
Keywords: natural circular frequency of undamped and damped of the system; linar differential equation second level; critical frequency; amplitude-frequency characteristics